Design and implementation of reduced number of switches for new multilevel inverter topology without zero-level state - Antar, Rakan Khalil; Hussein, Taha Ahmed; Abdullah, Abdallah Mohamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Currently, multilevel inverter (MLI) has been chosen over conventional inverter because of less harmonic distortions and higher output voltage levels. In this paper, 15 level inverter with reduced number of power switching devices is designed. Different output voltage levels can be obtained including zero level or with none zero level (NoneZero level). Single phase MLI inverter with 7 switches is built, simulated, and implemented practically. The system depending on modified absolute sinusoidal pulse width modulation (MASPWM) controller strategy is adopted. Simulation results clarified that MLI with NoneZero level provides output voltage with total harmonic distortion (THD) percent less than with zero level. The THD of the 15 level output voltage with zero level is 3.39%, while with NoneZero level is 3%, respectively. The system is tested at different output levels. The THD values at different output voltage levels is reduced by 12% depending on NoneZero level state. Depending on what has been achieved, the system has been implemented practically with NoneZero level and the THD value was 3.1%. These results prove the success of the suggested MLI circuit and MASPWM controller to obtain the required voltage level and THD.